Multidimensional Self-Propelled Motion Based on Nonlinear Science - Fujita, Risa; Matsuo, Muneyuki; Nakata, Satoshi (Frontiers in Physics, 2022)
Self-propelled objects, which exhibit characteristic features of motion, are proposed based on nonlinear science. At first, a self-propelled object with length like undulatory swimming is designed, i.e., the phase of oscillation at several points on the object is propagated in the opposite direction of motion. Second, the vertical oscillation of a camphor disk is created at an amphiphilic molecular layer developed on water. The proposed systems suggest that nonlinearity can enhance the autonomy of self-propelled objects as multidimensional motion.